If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -6 = 3x + -4 Reorder the terms: -6 + 1x = 3x + -4 Reorder the terms: -6 + 1x = -4 + 3x Solving -6 + 1x = -4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 1x + -3x = -4 + 3x + -3x Combine like terms: 1x + -3x = -2x -6 + -2x = -4 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + -2x = -4 + 0 -6 + -2x = -4 Add '6' to each side of the equation. -6 + 6 + -2x = -4 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = -4 + 6 -2x = -4 + 6 Combine like terms: -4 + 6 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| -[4(7)+2]-[3(7)-4]=x | | 4b+29=48 | | -[4(7)+2]-[3(7)-4]=-5 | | 3-21/7 | | y=3x+6graph | | 60=-5x+9 | | -(4y+2)-(-3y-4)=-5 | | 4+4y=8 | | 0=16t^2-30t+13 | | 6x-59=4x-9 | | 1+4y=8 | | 3(x+4x)=30-10x | | -2(10)+4=-8 | | 0=45-5t-5t^2 | | h=45-5t-5t^2 | | 59b^2+b=1 | | 16-5=14-10x | | (-2/5)x=8/15 | | 3(-3+0.3333333333y)-y=-9 | | -4.2=3x+25.8 | | 30/63 | | 49x^2+49y^2-42x+42y-18=0 | | 5h-8=2h+13 | | x-7.4=-5.7 | | 11x-15=6x | | -10x-4(3x-2)= | | -15+32=x | | y+32=17 | | (6x-1)-(3x-5)= | | n-13*3=12 | | 3t/7=14 | | X^2-2=x/6 |